Distanciamientos de siembra y su influencia en los componentes agronómicos y rendimiento de Lactuca sativa L., lechuga var. Great Lakes, en Zungarococha - Loreto.2021 - Nuñez del Prado Ruiz, Milagros Licett (2022)
The present experimental investigation "Planting spacings and their influence on the agronomic components and yield of Lactuca sativa L., lettuce var. Great Lakes, in Zungarococha- Loreto. 2022", belongs to the Faculty of Agronomy of the National University of the Peruvian Amazon located in the city of Iquitos, Maynas Province, Loreto Region, whose general objective was to determine the influence of planting spacings, on the agronomic components and yield of Lactuca sativa L., lettuce var. Great Lakes in Zungarococha-Loreto, using a Completely Randomized Block Experimental Design (DBCA). The treatments studied were: T1 (0.25 m x 0.25 m), T2 (0.30 m x 0.25 m), T3 (0.35 m x 0.25 m and T4 (0.40 m x 0.25 m); where it is concluded that the planting spacing influences the agronomic characteristics and yield in the cultivation of Lactuca sativa L., lettuce var. Great Lakes; the planting spacing 0.40 m x 0.25 m (T4), presented the best results in plant height (37 cm), plant diameter (38 cm), root length (5 cm), number of leaves / plant (11) head diameter (16 cm), total plant weight (330 g) and head weight (104 g); Treatment T4 (0.40 m x 0.25 m), presented the highest yield of head weight / ha with 6,240 Kg; Treatment T4 with (0.40 m x 0.25 m), had the best cost-benefit ratio of the crop with S/. 21,620.00.